Nudging businesses to pay their taxes: Does timing matter? - Christian Gillitzer; Mathias Sinning (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
This paper provides theoretical and empirical evidence on the implications of the timing of reminders by studying the effect of varying the timing of reminder letters to taxpayers on their payment behavior. The collection of unpaid tax debts constitutes a considerable challenge for tax authorities. We show that varying the timing of a reminder letter has a theoretically ambiguous effect on tax payments. We study the payment behavior of business taxpayers in a field experiment in Australia and find that a simple reminder letter increases the probability of payment by about 25 percentage points relative to a control group that does not receive a letter from the tax authority. However, variation over a three-week period in the timing of the reminder letter has no effect on the probability of payment within seven weeks of the due date. Our findings indicate that sending reminders early results in faster payment of debts with no effect on the ultimate probability of payment.
Keywords: C93; H25; H26; 330; tax compliance; business taxation; natural field experiment; behavioral insights